Identification of novel Tet(X6)-Tet(X2) recombinant variant in Elizabethkingia meningoseptica from a bullfrog farm and downstream river in China - Jin, Haobo; Jia, Qing; Jin, Xi; Zhu, Xinlong; Wang, Min-Ge; Sun, Ruan-Yang; Cui, Chaoyue (Frontiers in Microbiology, 2024)
The dissemination of strains producing tetracyclines monooxygenase Tet(X) from breeding farms to the natural environment poses a potential threat to public health. The aim of this study is to investigate the prevalence and distribution characteristics of tigecycline-resistant strains in typical bullfrog farming in China. Three tet(X)-producing Elizabethkingia meningoseptica strains were isolated from bullfrog breeding ponds, the sewage outlet, and downstream river in Zhejiang Province, China. These three strains exhibit a multidrug-resistant phenotype, displaying high level resistance to all 13 tested antibiotics, with sensitivity only to rifampicin. They carry a novel Tet(X) variant, differing from Tet(X6) by seven residues, and possess the ability to degrade tetracyclines.Interestingly, the novel Tet(X) is a recombinant variant formed by homologous recombination of Tet(X6) and the C-terminal of Tet(X2). Further analysis revealed that Tet(X6) formed several Tet(X) variants, including Tet(X5), through homologous recombination. The novel tet(X) gene is located on a circularizable integrative and conjugative element (ICEEmeChn3), with ISwz1 participating in the recombination of its multidrug resistance region, potentially facilitating the mobilization and recombination of tet(X) in early hosts. Moreover, these strains were clonally transmitted and shared a close genetic relationship (SNP< 62) with a clinically-sourced strain isolated from the same province. To our knowledge, this is the first report of homologous recombination between Tet(X) variants with differing activities. These clonal strains provide evidence of the transmission of tet(X)positive strains from aquaculture sewage to the natural environment, highlighting the need to strengthen the monitoring and management of this emerging farming model.